Defluoridation of drinking water using chemically modified bentonite clay - Kamble, Sanjay P.; Dixit, Priyadarshini; Rayalu, Sadhana S.; Labhsetwar, Nitin K. (Desalination, 2009)
Adsorption potential of metal oxide (lanthanum, magnesium and manganese) incorporated bentonite clay was investigated for defluoridation of drinking water using batch equilibrium experiments to gain insight of adsorption behavior, kinetics and mechanisms of adsorption of fluoride ion. The effect of various physicochemical parameters such as pH, adsorbent dose, initial fluoride concentration and the presence of interfering co-ions on adsorption of fluoride has been investigated. The 10%La-bentonite shows higher fluoride uptake capacity for defluoridation of drinking water as compared to Mg-bentonite, Mn-bentonite and bare bentonite clay. The uptake of fluoride in acidic pH was higher as compared to alkaline pH. The equilibrium adsorption data fitted reasonably well in both Langmuir and Freundlich isotherm models. It was also observed that in the presence of certain co-existing ions can have positive effect on removal of fluoride, while carbonate and bicarbonate anions show deleterious effect. The rate of adsorption was reasonably rapid and maximum fluoride uptake was attained within 30 min. The modified adsorbent material shows better fluoride removal properties for actual field water, which could be due to the positive effect of other co-ions present in the field water. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 10%La-bentonite; Defluoridation; Kinetic modeling; Langmuir and Freundlich adsorption isotherms; Water treatment

Destroying antimicrobial resistant bacteria (AMR) and difficult, opportunistic pathogen using cavitation and natural oils/plant extract - Mane, Maya B.; Bhandari, Vinay M.; Balapure, Kshama; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2020)
The present study reports, for the first time, a new and techno-economic strategy for effective removal of antimicrobial resistant bacteria (AMR) and difficult, opportunistic pathogen using cavitation and natural oils/plant extract. A hybrid methodology using natural oils of known health benefits has been discussed in combination with conventional physico-chemical method of hydrodynamic cavitation that not only provides efficient and effective water disinfection, but also eliminates harmful effects of conventional methods such as formation of disinfection by-products apart from reducing cost of treatment. A proof-of concept is demonstrated by achieving exceptionally high rates for practically complete removal of antimicrobial resistant (AMR) and relatively less researched, gram-negative opportunistic pathogen, Pseudomonas aeruginosa and gram-positive methicillin resistant, Staphylococcus aureus using a natural oil-Peppermint oil and two different cavitating reactors employing vortex flow (vortex diode) and linear flow (orifice) for hydrodynamic cavitation. > 99% disinfection could be obtained, typically in less than 10 min, using vortex diode with operating pressure drop of 1 bar and low dose of 0.1% peppermint oil as an additive, depicting very high rates of disinfection. The rate of disinfection can be further increased by using simple aeration which can result in significant lowering of oil dose. The conventional device, orifice requires relatively higher pressure drop of 2 bar and comparatively more time (similar to 20 min) for disinfection. The cost of the disinfection was also found to be significantly lower compared to most conventional processes indicating techno-economic feasibility in employing the developed hybrid method of disinfection for effectively eliminating bacteria including AMR bacteria from water. The developed approach not only highlights importance of going back to nature for not just conventional water disinfection, but also for eliminating hazardous AMR bacteria and may also find utility in many other applications for the removal of antimicrobial bacteria.
Keywords: AMR bacteria; Cavitation; Disinfection; Oil; Water treatment

Safe water and technology initiative for water disinfection: application of natural plant derived materials - Mane, Maya B.; Bhandari, Vinay M.; Ranade, Vivek V. (Journal of Water Process Engineering, 2021)
Safe drinking water is the necessity of life. The present study reveals use of natural resources such as plant extracts and natural oils for water disinfection. Differences between oil and water soluble additives were highlighted for plant extracts and insoluble natural oils. A hybrid hydrodynamic cavitation process was quite effective in both the cases and high rates of disinfection were achieved. Studies were reported using oils (ginger, turmeric, lavender, tulsi) and rhizome derived plant extracts such as ginger, turmeric and mango ginger, as additives in process intensification (0.1% v/V). A vortex based cavitation device (vortex diode, nominal capacity 1 m3/h) was used with pressure drop of 1 bar. A high disinfection of 96% and 88% was obtained in 15 min for ginger oil and mango ginger extract respectively as compared to 44% using cavitation alone. Acoustic cavitation gave 94% and 30% disinfection with and without additive-mango ginger extract. The FTIR analyses before and after cavitation, with ginger additive, showed no by-products formation and indicated gingerol as active component in disinfection. The per-pass disinfection values were also higher, up to 5 times than cavitation alone. Hybrid hydrodynamic cavitation using natural plant derived materials can offer a promising technology alternative in water disinfection.
Keywords: Cavitation; Disinfection; Natural oil; Plant extract; Water treatment

Studies in instant water disinfection using natural oils - Dixit, Divya; Bhandari, Vinay M.; Mane, Maya B.; Balapure, Kshama (Biochemical Engineering Journal, 2022)
The present research reveals an instant and simple process for drinking water treatment by employing specific natural oils having antimicrobial properties to ensure complete elimination of harmful bacteria. The disinfection was studied for two different model bacteria, Gram-negative E. coli and Gram-positive, S. aureus. Seven natural oils, ajwain, thyme, oregano, peppermint, harsingar, cinnamon leaf and black pepper oil were evaluated and were found to yield 100% water disinfection within 1 min except for harsingar and black pepper oil. The process was also effective for the instant and 100% disinfection of real well water. The methodology for altering zeta potential, to an extent of 130%, for instant disinfection in drinking water treatment helps in selecting natural oils. Molecular docking studies indicated natural oils action as potential inhibitors of bacterial DNA gyrase. The studies indicate one of the lowest operating costs comparable to conventional chlorination. The simple meth-odology not requiring complex equipment has the potential to provide many options for implementations-from portability, household application to large scale water treatment plants.
Keywords: Bacteria removal; Natural oil; Technology; Water treatment; Zeta potential